Use of CPAP Ventilation in Non-ICU Wards May Influence Outcomes in Patients with Severe Respiratory COVID-19 - Josip Brusić; Aron Grubešić; Filip Jarić; Tin Vučković; Andrica Lekić; Alan Šustić; Alen Protić (Medicina, 2024)
Background and Objectives: The COVID-19 disease has significantly burdened the healthcare system, including all units of severe patient treatment. Non-intensive care units were established to rationalize the capacity within the Intensive Care Unit (ICU) and to create a unit where patients with Acute Respiratory Distress Syndrome (ARDS) could be treated with non-invasive Continuous Positive Air Pressure (CPAP) outside the ICU. This unicentric retrospective study aimed to assess the efficacy of NIV Treatment in Patients of the fourth pandemic wave and how its application affects the frequency and mortality of ICU-treated patients at University Hospital Rijeka compared to earlier waves of the COVID-19 pandemic. Furthermore, the study showcases the effect of the Patient/Nurse ratio (P/N ratio) on overall mortality in the ICU. Materials and Methods: The study was conducted on two groups of patients with respiratory insufficiency in the second and third pandemic waves, treated in the COVID Respiratory Centre (CRC) (153 patients). We also reviewed a cohort of patients from the fourth pandemic wave who were initially hospitalized in a COVID-6 non-intensive unit from 1 October 2021 to 1 November 2022 (102 patients), and some of them escalated to CRC. Results: The introduction of the CPAP non-invasive ventilation method as a means of hypoxic respiratory failure treatment in non-intensive care units has decreased the strain, overall number of admissions, and CRC patient mortality. The overall fourth wave mortality was 29.4%, compared to the 58.2% overall mortality of the second and third waves. Conclusions: As a result, this has decreased CRC patient admissions and, by itself, overall mortality.